Economic outcomes associated with deep surgical site infection in patients with an open fracture of the lower limb. (November 2018) - Parker, B.; Petrou, S.; Masters, J. P. M.; Achana, F.; Costa, M. L.
Abstract : Aims: The aim of this study was to estimate economic outcomes associated with deep surgical site infection (SSI) in patients with an open fracture of the lower limb. Patients and Methods: A total of 460 patients were recruited from 24 specialist trauma hospitals in the United Kingdom Major Trauma Network. Preference-based health-related quality-of-life outcomes, assessed using the EuroQol EQ-5D-3L and the 6-Item Short-Form Health Survey questionnaire (SF-6D), and economic costs (£, 2014/2015 prices) were measured using participant-completed questionnaires over the 12 months following injury. Descriptive statistics and multivariate regression analysis were used to explore the relationship between deep SSI and health utility scores, quality-adjusted life-years (QALYs), and health and personal social service (PSS) costs. Results: Deep SSI was associated with lower EQ-5D-3L derived QALYs (adjusted mean difference -0.102, 95% confidence interval (CI) -0.202 to 0.001, p = 0.047) and increased health and social care costs (adjusted mean difference £1950; 95% CI £1383 to £5285, p = 0.250) versus patients without deep SSI over the 12 months following injury. Conclusion: Deep SSI may lead to significantly impaired health-related quality of life and increased economic costs. Our economic estimates can be used to inform clinical and budgetary service planning and can act as reference data for future economic evaluations of preventive or treatment interventions. Cite this article: Bone Joint J 2018;100-B:1506–10.